2006
DOI: 10.1029/2006gl026595
|View full text |Cite
|
Sign up to set email alerts
|

Substorm associated magnetotail energetic electrons pitch angle evolutions and flow reversals: Cluster observation

Abstract: The Cluster satellites observed a distinct pattern in the evolution of energetic electron pitch angle distributions on November 13, 2003, in the mid‐tail (radius >10RE) associated with intensifications of these electron fluxes that accompanied an observed local dipolarization of the magnetic field. The intensity of electrons (20–200 keV) were first observed to increase for perpendicular pitch angles (pancake distribution), then evolve into isotropic distributions, then further evolve into mixed distributions ‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 29 publications
3
73
1
Order By: Relevance
“…It has been shown that adiabatic betatron acceleration and Fermi acceleration are the mechanisms that energize electrons during dipolarization (Li et al, 1998;Ashour-Abdalla et al, 2011;Fu et al, 2011). However, there are some studies showing that adiabatic heating alone cannot account for the observed energy gain during substorm (Wu et al, 2006) might play some roles in electron energization at the fronts (Zhou et al, 2009). Whistler waves observed here might be able to efficiently accelerate electrons.…”
Section: Discussionmentioning
confidence: 73%
“…It has been shown that adiabatic betatron acceleration and Fermi acceleration are the mechanisms that energize electrons during dipolarization (Li et al, 1998;Ashour-Abdalla et al, 2011;Fu et al, 2011). However, there are some studies showing that adiabatic heating alone cannot account for the observed energy gain during substorm (Wu et al, 2006) might play some roles in electron energization at the fronts (Zhou et al, 2009). Whistler waves observed here might be able to efficiently accelerate electrons.…”
Section: Discussionmentioning
confidence: 73%
“…It has been reported by De Michelis et al [1999] that the plasma anisotropy in the near-Earth tail region is more often found during geomagnetic active periods. Other observations and analyses on the plasma anisotropy also suggest that the perpendicular ion anisotropy after dipolarizations in substorms were mainly caused by betatron heating when the magnetic field strength is strongly enhanced [Smets et al, 1999;Wu et al, 2006]. This mechanism is similar to the mechanism that produces anisotropy for energetic ions in the inner magnetosphere where the betatron acceleration plays an important role to increase ion perpendicular temperature [Liu and Rostoker, 1995;Woch et al, 1988].…”
Section: Discussionmentioning
confidence: 73%
“…The dominant Fermi acceleration on electrons was also found in AMPTE Ion Release Module (IRM) observations between 10 and 15 R E in the magnetotail [Sergeev et al, 2001]. Wu et al [2006] used Cluster observations to show the evolution of magnetotail energetic electron pitch angle distributions during substorms. They proposed a model in which Fermi acceleration dominated for electrons that were accelerated from the reconnection region, while betatron acceleration dominated for electrons accelerated from the near-tail region (inside of 10 R E in tail).…”
Section: Spatial Scale Of Mirror Structures and Electron Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, surveys show that field-aligned electron fluxes occur only a few percent of the observing time and are concentrated in the midnight to dawn sectors of the plasma sheet [e.g., Hada et al, 1981;Klumpar, 1993;Sugiyama et al, 1997]. While some investigations suggested an auroral source for the fieldaligned distributions [e.g., Klumpar et al, 1988;Klumpar, 1993], the consensus had developed that such distributions arise either locally or remotely from Fermi-type acceleration [e.g., Hada et al, 1981;Smets et al, 1999;Shiokawa et al, 2003;Vogiatzis et al, 2006;Wu et al, 2006]. Field-aligned electron fluxes have certainly been observed in the Earth's magnetosphere at low altitudes above the aurora and associated with particle acceleration in field-aligned potentials [e.g., Carlson et al, 1998;Marklund et al, 2001].…”
Section: Introductionmentioning
confidence: 99%